Prospective study to evaluate the safety of the world-first spot-scanning dedicated, small 360-degree gantry, synchrotron-based proton beam therapy system. (2nd January 2018) - Nishioka, Kentaro; Prayongrat, Anussara; Ono, Kota; Onodera, Shunsuke; Hashimoto, Takayuki; Katoh, Norio; Inoue, Tetsuya; Kinoshita, Rumiko; Yasuda, Koichi; Mori, Takashi; Onimaru, Rikiya; Shirato, Hiroki; et al.
Abstract: This is a report of a single-institution prospective study evaluating the safety of a spot-scanning dedicated, small 360-degree gantry, synchrotron-based proton beam therapy (PBT) system. Data collection was performed for 56 patients with 59 treatment sites who received proton beam therapy at Hokkaido University Hospital between March 2014 and July 2015. Forty-one patients were male and 15 were female. The median age was 66 years. The primary lesion sites were prostate ( n = 17), bone/soft tissue ( n = 10), liver ( n = 7), lung ( n = 6), central nervous system ( n = 5), colon ( n = 2), pancreas ( n = 2), kidney ( n = 2) and others ( n = 5). Chemotherapy was administered in 11 patients. The prescribed total dose was from 20 to 76 GyE (Radiobiological equivalent dose, RBE = 1.1), with the median dose of 65 GyE in 4 to 35 fractions. No PBT-related Common Terminology Criteria for Adverse Events Grade 4 or 5 toxicities were observed; the incidence of early PBT-related Grade 4 adverse events was 0% (95% confidence interval 0 to 6.38%). The most common Grade 3 toxicities were hematologic toxicity (12.5%) unlikely to be related to the PBT. One patient developed a left femoral neck fracture (Grade 3) at 14.5 months after PBT for chondrosarcoma of the left pelvis. The pathological findings showed no other malignancies, suggesting that it was possibly related to the PBT. In conclusion, the spot-scanning dedicated, synchrotron-based PBT system is feasible, but further studies on its long-term safety and efficacy are warranted.